PROGRAM BERBAHASA WALIKAN DI JTV MALANG - Yulistiowati, Irma Mufita (Universitas Merdeka Malang, 2018)
Abstract News program is a review of facts and events reports that have news value that is unusual, factual, essential, and broadcast through the media periodically. Local television efforts to attract the audience is presenting the language of the people of Malang, the language of Walikan by reversing the word from behind. This research uses descriptive qualitative method with the presentation of descriptive analysis in the form of language, the way the subject of research is concerned with the problem under study which is also the data. Qualitative data can be words, sentences or narratives, both obtained from in-depth interviews and observations. Local television news program in preserving the language walik Malang City also through some process in its production that is looking for news. Furthermore, the stages of collecting news materials and the stage of writing a news script through the stage of editing news and views. Analysis of local television news programs in preserving the language walik Malang has been successfully seen from the intensity of news provided and the content of existing news. And the technique of presenting the news in such a way as to use the Malangan Language to make interesting and impact the preservation of malangan language in the community indirectly. From non technical aspects related to the close communication between news crew. Analysis of feedback from JTV Malang Bureau viewers is also very necessary in maintaining, to be able to continue to preserve the culture of malangan language for later generations. Keywords : News, Walikan Language and Local Television.DOI :Â https://doi.org/10.26905/nomosleca.v4i2.2544